Monetary policy, financial regulation and financial stability: A comparison between the Fed and the ECB - Gunther Schnabl; Nils Sonnenberg (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2020)
The paper analyses in light of Austrian and Keynesian economic theory the impact of conventional and unconventional monetary policies as therapies for financial crises. It compares the financial market stabilization measures of the Federal Reserve System and the European System of Central Banks in response to the US subprime crisis and the European financial and debt crisis. It is shown that the Federal Reserve System's crisis measures were more directed towards stabilizing the banking system, whereas the European Central Bank had a stronger focus on the stabilization of the debt affordability of euro area crisis countries. In both cases, household credit growth remained under control despite renewed monetary expansion, while new imbalances emerged in the corporate sector. In the euro area, loose monetary policy had a destabilizing impact on the financial sector.
Keywords: B53; E12; E14; E30; E44; E58; G10; G20; H30; H50; 330; Financial cycles; financial crisis; financial stability; Hayek; Keynes; monetarypolicy